Bridging Norms and Practice: Structural Barriers to Women’s Protection from Sexual Violence in Nigeria - Abubakar Muhammad jibril; Lamin Saidy Jeng (Pancasila and Law Review, 2025)
Sexual violence persists in Nigeria despite ratification of major human rights treaties and enactment of domestic legislation such as the Violence Against Persons (Prohibition) Act. This study assesses whether Nigeria’s legal and institutional frameworks provide effective protection for women, focusing on constitutional dualism, uneven state implementation, socio-cultural resistance, and under-resourced enforcement bodies. Using a qualitative normative legal analysis, it examines treaty domestication, limitations in enforcement of the VAPP Act, and structural barriers faced by survivors, drawing comparative insight from South Africa’s monist constitutional model. The study finds that fragmented criminal regimes and institutional weaknesses undermine compliance with international obligations and argues for a monist constitutional approach, harmonized national standards, and strengthened institutional capacity to align domestic practice with human rights commitments.